2013
DOI: 10.1111/jce.12159
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Pacing Strategies to Minimize Phrenic Nerve Stimulation in Cardiac Resynchronization Therapy

Abstract: Introduction Phrenic nerve (PN) stimulation (PNS) frequently limits cardiac resynchronization therapy (CRT). Yet, pacing strategies to minimize PNS have not been systematically compared. We propose to: 1) compare different pacing strategies to minimize PNS in CRT and 2) evaluate differences between PN and left ventricular (LV) capture thresholds among LV pacing configurations. Methods and Results PN and LV thresholds were obtained using 6 LV configurations in 28 patients with any PNS during CRT implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Differences in chronaxie between the phrenic nerve and ventricular myocardium have been exploited to avoid phrenic nerve capture at longer pulse widths for coronary sinus leads. 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in chronaxie between the phrenic nerve and ventricular myocardium have been exploited to avoid phrenic nerve capture at longer pulse widths for coronary sinus leads. 3 , 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Differences in chronaxie between the phrenic nerve and ventricular myocardium have been exploited to avoid phrenic nerve capture at longer pulse widths for coronary sinus leads. [3][4][5] Jastrzębski et al studied strength-duration curves for HBP in 127 patients and found lower chronaxie for the His bundle compared to local RV myocardium in patients with S-HBP (whereas chronaxie did not differ in patients with obligatory NS-HBP). 6 As a result, S-HBP is facilitated with pacing at shorter pulse width.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…With coronary sinus lead placement, phrenic stimulation affects approximately 15% to 30% of patients (14,15), requiring either repositioning the lead or electrically reprogramming another vector, both of which may result in lead dysfunction (16,17). Detecting phrenic stimulation at implantation has poor sensitivity due to positional dependency (18) calling for alternative strategies for preventing stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Another area where knowledge of strength-duration curves for the HB might play a role is the achievement of selective vs nonselective HB capture. A few studies reported that differences in chronaxie values enable selective pacing of different tissues from the same electrode by using a different combination of pulse widths and voltage output [12][13][14][15] ; whether this is also the case with HB/RV myocardium capture is not known.…”
Section: Introductionmentioning
confidence: 99%